Complexation and Catenation in Aqueous Media Using a Self‐Assembled PdII Metallacyclic Receptor. Issue 26 (1st June 2015) - Rama, Tamara; López‐Vidal, Eva M.; García, Marcos D.; Peinador, Carlos; Quintela, José M.
Abstract A M2L2 rectangular‐shaped metallacycle, obtained by metal‐directed self‐assembly of a 2‐(pyridin‐4‐ylmethyl)‐2, 7‐diazapyrenium salt and [(en)Pd (NO3)2] (en=ethylenediamine), has been investigated as a molecular receptor for a wide range of aromatic substrates in water. Complexation and catenation of the receptor with selected mono‐ and polycyclic aromatic substrates produced 1:1 inclusion complexes and [2]catenanes in a highly efficient fashion, as determined by NMR and UV/Vis spectroscopic techniques, as well as single‐crystal X‐ray crystallography. Furthermore, the thermodynamic and kinetic features of the complexation processes have been analyzed for selected model guests.